Characterization of a Novel Putative S-Adenosylmethionine Decarboxylase-Like Protein from Leishmania donovani - Singh, Saurabh Pratap; Agnihotri, Pragati; Pratap, J. Venkatesh (PLOS ONE, 2013)
In addition to the S-adenosylmethionine decarboxylase (AD) present in all organisms, trypanosomatids including Leishmania spp. possess an additional copy, annotated as the putative S-adenosylmethionine decarboxylase-like proenzyme (ADL). Phylogenetic analysis confirms that ADL is unique to trypanosomatids and has several unique features such as lack of autocatalytic cleavage and a distinct evolutionary lineage, even from trypanosomatid ADs. In Trypanosoma ADL was found to be enzymaticaly dead but plays an essential regulatory role by forming a heterodimer complex with AD. However, no structural or functional information is available about ADL from Leishmania spp. Here, in this study, we report the cloning, expression, purification, structural and functional characterization of Leishmania donovani (L. donovani) ADL using biophysical, biochemical and computational techniques. Biophysical studies show that, L. donovani ADL binds S-adenosylmethionine (SAM) and putrescine which are natural substrates of AD. Computational modeling and docking studies showed that in comparison to the ADs of other organisms including human, residues involved in putrescine binding are partially conserved while the SAM binding residues are significantly different. In silico protein-protein interaction study reveals that L. donovani ADL can interact with AD. These results indicate that L. donovani ADL posses a novel substrate binding property and may play an essential role in polyamine biosynthesis with a different mode of function from known proteins of the S-adenosylmethionine decarboxylase super family.